2022
DOI: 10.1007/s10763-022-10254-w
|View full text |Cite
|
Sign up to set email alerts
|

Student, Teacher, and Scientist Views of the Scientific Enterprise: An Epistemic Network Re-analysis

Abstract: There is substantial research in science education about students’, teachers’, and scientists’ views of nature of science (NOS). Many studies have used NOS frameworks that focus on particular ideas such as tentativeness of scientific knowledge and cultural embeddedness of science. In this paper, we investigate NOS from the perspective of the Family Resemblance Approach (FRA) which considers clusters of ideas about science in terms of categories that offer a comprehensive analytical lens to studying NOS views. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 36 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Although some research is available in this area (e.g. Peters-Burton et al, 2022 ), the potential of FRA for tracing of students’ as well as teachers’ progression given particular interventions of learning has not yet been explored. Finally, one of the outcomes of our review was the identification of research that focused on a range of research instruments in identifying NOS understandings including, for example the use of drawings in tracing pre-service teachers’ drawings about NOS (Erduran et al, 2020 ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some research is available in this area (e.g. Peters-Burton et al, 2022 ), the potential of FRA for tracing of students’ as well as teachers’ progression given particular interventions of learning has not yet been explored. Finally, one of the outcomes of our review was the identification of research that focused on a range of research instruments in identifying NOS understandings including, for example the use of drawings in tracing pre-service teachers’ drawings about NOS (Erduran et al, 2020 ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Peters-Burton & Baynard, 2013 ; Cheung & Winterbottom, 2021 ) and it has been used in previous studies on FRA (e.g. Caramaschi et al, 2022 ; Author, 2020 ; Peters-Burton et al, 2022 ). ENA visualizes the co-occurrences between two codes in a stanza (Shaffer, 2017 ), which was defined as one single study identified in the systematic review procedure.…”
Section: Methodsmentioning
confidence: 99%
“…The research capability of a university teacher is the ability to contribute to the existing body of knowledge and actively participate in research activities (Peters-Burton, Dagher & Erduran, 2023). In addition to their duties as instructors, educators are encouraged to explore new frontiers of knowledge in their respective disciplines.…”
Section: Introductionmentioning
confidence: 99%